Asymmetric Information and Sovereign Debt: Theory Meets Mexican Data - Cole, Harold; Neuhann, Daniel; Ordoñez, Guillermo (Journal of Political Economy, 2022)
Using bid-level data from discriminatory auctions for Mexican government bonds, we demonstrate that asymmetric information about default risk is a key friction in sovereign bond markets. We document that large bidders achieve higher bid-acceptance rates than other bidders despite paying no more for executed bids. We then propose a new model of primary markets in which investors may differ in wealth, risk aversion, market power, and information. Only asymmetric information can qualitatively account for our empirical finding, and asymmetric information about rare disasters can quantitatively match bidding and yield moments. Counterfactuals reveal substantial effects of asymmetric information on yields.